2005
DOI: 10.1108/14626000510594647
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and education in Austrian secondary schools

Abstract: PurposeEntrepreneurship is defined as a “life skill”, and the European Union (EU) has recently called on member states to promote the development of entrepreneurial attitudes from primary school right through to university level. The paper aims to investigate which factors influence entrepreneurial thinking and attitudes towards entrepreneurship in vocational and general secondary education in Austria.Design/methodology/approachThe paper is based on the configuration approach. This approach was adapted as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 7 publications
4
36
0
Order By: Relevance
“…Ismail et al (2009) point out that since future entrepreneurs can be found amongst those who are currently undergoing their educational process at the universities, entrepreneurship education is one of the most effective ways to promote the transition of graduates into the world of entrepreneurship. Frank et al (2005) note that entrepreneurship education seeks to propose people, especially young people, to be responsible, as well as enterprising individuals who became entrepreneurs or entrepreneurial thinkers who contribute to economic development and sustainable communities. Kolvereid (1996), Mazzarol et al (1999 and Peterman and Kennedy (2003) find a positive relationship between prior work experience in a small business environment and attitudes toward entrepreneurship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ismail et al (2009) point out that since future entrepreneurs can be found amongst those who are currently undergoing their educational process at the universities, entrepreneurship education is one of the most effective ways to promote the transition of graduates into the world of entrepreneurship. Frank et al (2005) note that entrepreneurship education seeks to propose people, especially young people, to be responsible, as well as enterprising individuals who became entrepreneurs or entrepreneurial thinkers who contribute to economic development and sustainable communities. Kolvereid (1996), Mazzarol et al (1999 and Peterman and Kennedy (2003) find a positive relationship between prior work experience in a small business environment and attitudes toward entrepreneurship.…”
Section: Resultsmentioning
confidence: 99%
“…Raposo and Depaco (2011) point out that entrepreneurial attitudes are not only required in the course of a classic entrepreneurial career, but they are also in high demand independent employment relationships. Frank et al (2005) note that entrepreneurship education seeks to propose people, especially young people, to be responsible, as well as enterprising individuals who became entrepreneurs or entrepreneurial thinkers who contribute to economic development and sustainable communities. Entrepreneurship education is aimed at creating or increasing entrepreneurial attitudes, spirit and culture among individuals and in the general community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurship education aims at building entrepreneurial competencies, which are considered as combinations of the different skills, knowledge and attitudes" point out that the two important objectives of entrepreneurship education programmes are (1) to increase the awareness and understanding of the process involved in initiating and managing a new business, and (2) to increase students' awareness of small business ownership as a serious career option. Frank et al (2005) agree that entrepreneurship education aims at creating or increasing entrepreneurial attitudes, spirit and culture among individuals and in the general community. Entrepreneurship education is associated with opportunity recognition, venture creation and growth.…”
Section: The Meaning Of Entrepreneurship Educationmentioning
confidence: 99%
“…Entrepreneurship has become a widely taught subject in universities and business schools, therefore graduates with an entrepreneurship major are more likely to start new businesses and have stronger entrepreneurial intentions than other graduates [8]. Many factors have influenced entrepreneurial thinking and attitudes towards entrepreneurship in vocational schools [9]. A critical evaluation of the literature on entrepreneurship education highlighted a number of inherent definitional, conceptual and contextual issues relating to this area of research.…”
Section: B Entrepreneur In Educationmentioning
confidence: 99%